Telegram Chatbot-Based Interactive Media in Fourth Grade Elementary School Indonesian Language Subjects - Cahyani, Wita Eka Putri; Sismulyasih SB, Nugraheti; Purwati, Panca Dewi (LPPM Undiksha, 2024)
Lack of media use causes students to be passive, resulting in low interest in learning and making student learning outcomes less than satisfactory. This research aims to develop Telegram Chatbot-Based Interactive Media in Indonesian Language Subjects for fourth-grade elementary school students. This type of research is developed using the Sugiyono model in eight stages. The subjects of this research were a fourth-grade teacher, 1 material expert, 1 media expert, 6 initial trial students, and 14 usage trial students. The methods used to collect data are observation, interviews, questionnaires, and tests. The data collection instruments were observation guidelines, interview sheets, and test questions. Data analysis techniques used qualitative descriptive analysis, quantitative descriptive analysis, N-Gain analysis, and inferential statistical analysis (t-test). The research results were the material expert assessment results of 92.3% (very feasible). The results of the media expert assessment were 90.8% (very feasible). The results of the teacher response percentage were 95% (very feasible). The result of the percentage of student responses of 94.15% falls into the very feasible category. The N-Gain test result of 0.6949 is included in the medium criteria. The t-test results showed significant differences in student learning outcomes after taking part in learning using interactive media based on the Telegram chatbot. It was concluded that interactive media based on the Telegram chatbot was suitable and adequate for subjects of the Indonesian language. The research implication is that Telegram chatbot-based interactive media can be used in learning Indonesian.